The perceptions of tertiary students and lecturers regarding CLIL-based critical reading material employing interactive multimedia - Fitrawati Fitrawati; Hermawati Syarif; Muhammad Zaim; David D Perrodin (Universitas Pendidikan Indonesia, 2023)
Content and Language Integrated Learning (CLIL), a methodology for teaching and learning content via a foreign language, has become a promising method for developing critical reading material and fostering students' analytical thinking and reasoning abilities in higher education. Numerous studies have examined the development of critical reading teaching materials, yet only some have focused on developing and implementing CLIL-based strategies in higher education. Therefore, this article explores the perceptions of English students and lecturers on implementing CLIL-based principles with interactive multimedia in developing critical reading material in higher education. The study collected data from students and teachers through questionnaires using a descriptive quantitative method. The closed-ended responses were analyzed by frequency and proportion, and compared between groups using the Mann-Whitney U test. Open-ended responses were categorized and analyzed through a matrix checklist to study a key variable or topic of public interest. The findings showed that most students believed that CLIL-based critical reading material using interactive multimedia enhanced their analytical thinking and reasoning abilities concerning the subject content. They also believed their learning outcomes would improve. All lecturers believed that the need for CLIL-based critical reading material employing the integration of interactive multimedia is essential, especially in an online learning setting. Furthermore, the lectures stated that engaging with critical reading material using interactive multimedia in the classroom increased the students’ motivation, promoting interaction among students and developing essential logical and cognitive competencies. Overall, the student and lecturer groups corroborated the need to further implement CLIL-based critical reading material development by using interactive multimedia in higher education.